Tax Bunching, Income Shifting and Self-employment - Daniel Le Maire; Bertel Schjerning (University of Copenhagen, Economic Policy Research Unit (EPRU), 2012)
This paper proposes a dynamic extension to Saez (2010) bunching formula that allows us to distinguish bunching based on real responses and income shifting. We provide direct evidence of income shifting and pronounced bunching in taxable income for the case of Danish self-employed. If income shifting was neglected in this case, we would conclude that taxable incomes were highly sensitive to changes in marginal tax rates. We show, however, that more than half of the observed bunching in taxable income for the self-employed is driven by intertemporal income shifting, implying a structural elasticity in the range of 0.14-0.20
Keywords: H20; J20; 330; Self-employment; tax bunching; retained pro?ts; tax avoidance; income shifting; Gewinnverlagerung; Steuervermeidung; Selbstständige; Dänemark